Aquilegia yangii (Ranunculaceae), a new species from western China - Li, Lu; Luo, Yan; Yang, Chen-Xuan; Deng, Jian-Ping; Erst, Andrey S. (Phytotaxa, 2018)
Aquilegia yangii (Ranunculaceae), a new species from western China, is described and illustrated. The new species is similar to A. oxysepala and A. kansuensis. However, there are differences in reproductive structure, especially flower size, petal shape, anther colour and seed surface, between the new species and the other two species. The seed surface morphology of the new species is also described in this study.